1996
DOI: 10.1111/j.1530-0277.1996.tb01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nicotine on Myocardial Stiffness and Fibrosis During Chronic Ethanol Use

Abstract: Cardiomyopathy related to ethanol abuse is often accompanied by cigarette use. To examine if the major cardioactive component may intensify the abnormal function and composition induced by chronic ethanol, nicotine was administered orally, 2.5 mg bid, to a canine model receiving 36% of calories as ethanol for 6 months (group III). These animals were compared with group II receiving ethanol alone, group IV on nicotine alone, and controls (group I). In the intact, ventilated, anesthetized dog, left ventricular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…With the design of this study, only a retrospective approach for the drinking habits of all donors by the family members was possible. Since alcoholic donors had significantly higher active smoking consumption compared to the other groups, we cannot exclude an additional noxious effect of nicotine in the myocardium as reported in experimental (Rajiyah et al, 1996) and clinical studies (Zakhari, 1991), although nicotine heart effect mainly induces coronary artery lesions. Evaluation of myocardial apoptosis is limited to TUNEL, BAX, and BCL-2 activities.…”
mentioning
confidence: 77%
“…With the design of this study, only a retrospective approach for the drinking habits of all donors by the family members was possible. Since alcoholic donors had significantly higher active smoking consumption compared to the other groups, we cannot exclude an additional noxious effect of nicotine in the myocardium as reported in experimental (Rajiyah et al, 1996) and clinical studies (Zakhari, 1991), although nicotine heart effect mainly induces coronary artery lesions. Evaluation of myocardial apoptosis is limited to TUNEL, BAX, and BCL-2 activities.…”
mentioning
confidence: 77%
“…The increased elastic modulus due to nicotine might be related to increased synthesis of collagen or reduced production of matrix metalloproteinase. It has been reported that nicotine leads to increased collagen synthesis in beagles (Ahmed et al 1976) and that nicotine causes an increase in cross-linked collagen content, resulting in fibrosis of the myocardial interstitium in dogs (Rajiyah et al 1996). Thus, increased collagen synthesis or increased cross-linked collagen content of fibroblasts might induce increased elastic modulus due to nicotine administration in the tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycosylation of collagen observed in this diabetic model is presumed to provide cross-links that confer enhanced stiffness to the protein, a process also observed in pathologic states in which nonglucose adducts are likely to be involved (29). Although characterized by fluorescence of collagen, other glycosylated products may be elicited by diabetes.…”
Section: Collagen Glycationmentioning
confidence: 97%